Tailoring Nutrition Literacy Scale for Rural Women: Development and Validation - Kumari, Jagriti; Basavaprabhu Jirli; Arun Kumar Singh; Prashish Singh; M. Chennamadhava; Harshit Paliwal (Indian Journal of Extension Education, 2025)
Nutrition literacy (NL) is essential for fostering and sustaining healthy dietary behaviours. However, data on NL among rural women in India are limited, and existing measurement tools lack cultural appropriateness for this population. To address this gap, this study conducted during 2024–2025, developed and validated the Nutrition Literacy Scale for Rural Women (NLS-RW), measuring; cognitive, functional, interactive, and critical domains of NL. An initial pool of 100 statements was generated and then refined to 95 items. Relevancy testing with 60 subject matter experts using a five-point scale informed retention decisions was performed based on relevancy percentage (RP), relevancy weightage (RW), and mean relevancy score (MRS). Item analysis with a sample of 64 rural women aged 15–49 years from three districts of Jharkhand (Chatra, Ranchi, and Khunti) was conducted. Reliability was assessed using split-half correlation (Spearman–Brown adjustment) and Cronbach’s alpha. Content validity yielded a scale-level content validity index (S-CVI/Ave) of 0.92, indicating excellent content validity. The final scale comprised 57 items and showed excellent internal consistency (Cronbach’s α = 0.948; Spearman–Brown coefficient = 0.968). The NLS-RW comprehensively captures multiple dimensions of nutrition literacy among rural women.